Pengaruh Tingkat Kesehatan Bank Terhadap Firm Value Dengan CSR Expenditure Sebagai Variabel Moderasi - Bijak, Abdillah; Soemantri, Roebiandini; Soenaria, Syaiful Rahman (Owner : Riset dan Jurnal Akuntansi, 2024)
This research investigates the influence of various financial variables on Bank Health Level on Company Value (PBV) with CSR Expenditure as a moderating variable in the context of the banking industry in Indonesia. The research method used in this research is descriptive and verification research, while the sampling technique used is non-probability sampling with a purposive sampling method, the sample for this research is 26 companies. This research identifies Non-Performing Loans (NPL) and Return on Assets (ROA) as factors that influence Price to Book Value (PBV). Then CSR Expenditure can moderate the Non-Performing Loan (NPL), Loan Deposit Ratio (LDR), and Good Corporate Government (GCG) variables on price-to-book value (PBV). Simultaneously, the results of the F test show that collectively these variables have a significant effect on Price to Book Value (PBV), and CSR Expenditure is an important factor that contributes positively to Price to Book Value (PBV), which can be concluded that CSR policy is very capable strengthening company performance in increasing stakeholder perception and trust which is reflected in increasing company value.